„Człowiek jest pierwszy, najważniejszy, na człowieku buduje się wszystko” – w kręgu myśli społecznej kard. Stefana Wyszyńskiego - Drozdowski, Mariusz (Społeczeństwo, 2022)
In this article, I wanted to look at cardinal Stefan Wyszyński as a person of action through the prism of what he himself said about man. From among the primate’s many homilies and speeches, I chose ten sentences that deal with issues of faith, nation, forgiveness, morality, passing time. Fragmentary statements about man and humanity, in this form, resemble Christian meditation rather than strictly speaking, scientific discourse. Therefore, the subject presented by me should be understood as a reflection on the human condition in a wide range of theological, philosophical and social issues.